Tropical rainforest silviculture: a research project report - Synnott, T (Commenwealth Forestry Institute, University of Oxford, 1977)
This report describes the results of a research project concerned with silyiculture and management of tropical rainforest. Data from silvicultural treatment experiments were analysed to examine the effects of logging and treatments on growth rates and yields. It was shown that diameter increments, and basal area and volume production, were strongly affected by reductions in stocking resulting from logging and treatment. Various computer programs were developed and adapted for processing data from recurrent measurements of rainforest plots, including versions suitable for small computers. New programs were developed to find ways of using such data for making more reliable forecasts of future stocking and yields in rainforest, and were shown to be feasible and very promising for management and research purposes. The results of the project, and their practical implications for management and research, are presented and discussed.